دور المحافظ العقاري في إجراء الصلح والآثار المترتبة عليه - -فضيلة جابر (Universté ELOUEd-جامعة الوادي, 2020)
المحافظ العقاري هو موظف عمومي تابع لوزارة المالية، يتولى تسيير مصلحة إدارية يطلق على تسميتها المحافظة العقارية،أسند إليه المشرع الجزائري مهاموصلاحيات متعددة، وتبرز مهامه في إطار عملية الشهر العقاري عقب الانتهاء من أعمال المسح العام للأراضي أين يبدأ بتأسيس السجل العقاري، فيقوم بترقيم العقارات الممسوحة وينشئ البطاقات العقارية ويقوم بتسليم الدفتر العقاري لأصحاب الحقوق ،كما أنه يفحص الشروط القانونية التي تتطلبها عمليات الشهر وقد منحه المشرع أثناء مراقبته للمحررات المودعة أمامه سلطة قبول تنفيذ إجراء الشهر أورفض تنفيذه . لقد منح المشرع الجزائري للمحافظ العقاري سلطة واسعة بمناسبة قيامه بعمليات الترقيم المؤقت تتمثل في إجراء الصلح بين المتخاصمين عند النظر في الإحتجاجات والإعتراضات المقدمة من الأشخاص المتضررين من أعمال الترقيم المؤقت والتي تتوج إما بمحضر المصالحة أوعدم المصالحة ولا يكون أمام المتضرر في حالة فشل محاولة الصلح إلا سلوك طريق القضاء. The real estate governor is public official of the ministry of finance, he is running an administrative service called the estate governor, an Algerian projects, tasks and multiple powers have been entrusted to him, it’s function are highlighted within the framework real-estate month process following the completion of general survey of the land where the establishment of the land begins property register he numbers the scanned properties create real estate, cars and delivers the real estate book for owners. it also examines the legal requirements for operations in the month and you have given the projects while it controls on engines deposited with the acceptance authority of the month procedure of the refused to implement it The Algerian real estate project has been given wide authority on the occasion of his temporary numbering, the reconciliation procedure between two bickering when considering the protests person from the temporary numbering works, which culminate in either the reconciliation minute or non-reconciliation .the adversaries the event of failure attempted reconciliation is only the way of justice.
مذكرة ماستر
Keywords: المحافظة العقارية; running an administrative service called the estate governor